PENGARUH INDEPENDENSI, KOMPETENSI, DAN ETIKA PROFESI TERHADAP PROFESIONALISME AUDITOR BPKP PERWAKILAN PROVINSI SUMATERA UTARA - Lubis, Hazman Fakhri; -, Andreas; -, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
There are some factors influencing the auditors’ professionalism. This study attempts to obtain empirical evidence the influence of independency, competency, and professional ethics auditor professionalism, especially those who are working in BPKP North Sumatera.The population of study is all auditors who worked on the BPKP North Sumatera. Methods of data collection in this study is the method of questionnaire survey using instruments that are delivered directly to the BPKP Representative North Sumatera Province. The Respondents are used in the analysis were 80 respondents (80%) Methods of Analysis is conducted with a multiple regression analysis.The results of testing that has been done.Partial regression test (t test) showed that the auditors’ independency, competency, and proffesional ethics had a influences towards auditor professionalism. The coefficient of determination in this study was 53,9 %. These four variables affect the dependent variable was 53,9 %, while 46,1 % is influenced by other variables that are not addressed in this study.Keyword: independency, competency, proffesional ethics, and professionalism